Psikologi Pendidikan Sebagai Kompetensi Dasar Pendidik dan Tenaga Kependidikan - Elsa Nuraidah; Dede Nurhida; Neni Eliawati (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Education is the interaction between educators and students. Educational interaction is always related to knowledge, developing potential, and inculcating values, either through the learning process, guidance or training. In this interaction the individual behaves, and the behavior becomes the subject of educational psychology studies. Thus educational psychology is a science that examines the behavior of a person (especially students) in interacting with the educational environment. A teacher is obliged to understand educational psychology, considering that teachers interact with students and also other people, more often than not, in the educational process.